Comparison of statistical methods for detection of serum lipid biomarkers for mesothelioma and asbestos exposure. (July 2017) - Xu, Rengyi; Mesaros, Clementina; Weng, Liwei; Snyder, Nathaniel W; Vachani, Anil; Blair, Ian A; Hwang, Wei-Ting
Aim: We compared three statistical methods in selecting a panel of serum lipid biomarkers for mesothelioma and asbestos exposure.Materials & methods: Serum samples from mesothelioma, asbestos-exposed subjects and controls (40 per group) were analyzed. Three variable selection methods were considered: top-ranked predictors from univariate model, stepwise and least absolute shrinkage and selection operator. Crossed-validated area under the receiver operating characteristic curve was used to compare the prediction performance.Results: Lipids with high crossed-validated area under the curve were identified. Lipid with mass-to-charge ratio of 372.31 was selected by all three methods comparing mesothelioma versus control. Lipids with mass-to-charge ratio of 1464.80 and 329.21 were selected by two models for asbestos exposure versus control.Conclusion: Different methods selected a similar set of serum lipids. Combining candidate biomarkers can improve prediction.